1990
DOI: 10.1128/jb.172.4.1939-1947.1990
|View full text |Cite
|
Sign up to set email alerts
|

Complex character of senS, a novel gene regulating expression of extracellular-protein genes of Bacillus subtilis

Abstract: The senS gene of Bacillus subtilis, which in high copy number stimulates the expression of several extracellular-protein genes, has been cloned, genetically mapped, and sequenced. The gene codes for a highly charged basic protein containing 65 amino acid residues. The gene is characterized by the presence of a transcription terminator (attenuator) located between the promoter and open reading frame, a strong ribosome-binding site, and a strong transcription terminator at the 3' end of this monocistronic gene. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

1991
1991
2005
2005

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 53 publications
1
19
0
Order By: Relevance
“…Similar organizations have been reported in at least three other cases, i.e., sacB (32) and senS (38) in B. subtilis and bgl (26) in E. coli. The transcription terminator-like structure has been demonstrated to function as a regulatory device in controlling the induction of sacB, the structural gene for levansucrase (28,31,48).…”
Section: Resultssupporting
confidence: 60%
See 2 more Smart Citations
“…Similar organizations have been reported in at least three other cases, i.e., sacB (32) and senS (38) in B. subtilis and bgl (26) in E. coli. The transcription terminator-like structure has been demonstrated to function as a regulatory device in controlling the induction of sacB, the structural gene for levansucrase (28,31,48).…”
Section: Resultssupporting
confidence: 60%
“…In the third case, senS, a homolog of senN, also carries an upstream terminatorlike structure. If the terminatorlike structure is deleted, it is lethal for B. subtilis (38). For the ten operon, the presence of the terminatorlike structure reduces the expression of the operon.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several regulatory genes encoding small polypeptides of 46 to 65 amino acid residues which cause a higher level of expression of a class of extracellular proteins in B. subtilis have been reported, i.e., senS (45), degR (25,42,49), and degQ (3,48). The pleiotropic effects of these genes suggest that they are part of a global control mechanism affecting the synthesis of degradative enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…The authors later identified the B. subtilis counterpart of senN named senS that also functions as a positive regulator of aprE expression. SenS is a positively charged, 65-amino-acid protein with a helix-turn-helix motif in the molecule (25). It was demonstrated that SenS exerts its positive effect by acting on the region between nt Ϫ177 and Ϫ415 upstream of the transcription start site of aprE (5), but further details, including the target of SenS and the relationship with the other transcriptional regulators, have not been investigated.…”
mentioning
confidence: 99%